ELECTRONIC SPARK ADVANCE IGNITION SYSTEM SIMULATOR AS INSTRUCTIONAL MEDIA FOR ASSISTING ELECTRICAL PRACTICES ON AUTOMOTIVE FIELD - Tafakur Tafakur; Moch Solikin (Universitas Sultan Ageng Tirtayasa, 2018)
This paper discusses the development of simulators as instructional media for learning Electronic Spark Advance System in vehicle technology and its advisability. Simulators were developed to assist students in learning the skills and practical knowledge of the electronic ignition system in vehicle engine. The simulator was developed by applying 10 development stages. Development stages included: analyzing the problems, needs analysis, product design, design implementation, expert assessment, limited testing (small classes), product revisions, large usage / class testing, product revisions, and get suitable product. The development result was a replica of ESA system separated from vehicle system. The ignition system components were arranged on the acrylic board, so it can be used by the students safely and easily for: (1) identifying components, (2) inspect components, (3) inspect ignition circuit, (4) conducting ignition system adjusting, and (5)simulating ignition system. Based on the material and learning media aspects with the results of limited trials as well as usage trials show that the developed ESA's electronic ignition system simulator was suitable to use, so it can help students to learn and practice skills related to maintenance jobs and repair ESA's electronic ignition system more easily.